The Effect of Village Fund Allocation on Village Development and Society Welfare - Citra Intan Harum Permata; M. Muchson; Bayu Surindra (CV. AFDIFAL MAJU BERKAH, 2022)
This research is motivated by problems in different villages, development and society welfare are based on the distribution of village funds. This makes village governments dependent on central government funding. This study intends to determine (1) the effect of Village Fund Allocation with village development. (2) the influence between the Village Fund Allocation and the welfare of the society. (3) the influence between Village Fund Allocation with Village Development and society welfare. In this study the approach used is quantitative, while the survey method is the method used in this study. The sample used was 15 people from 12 villages located in Semen District, so that the total sample was 180 people. Methods of data collection using a questionnaire. In this study, data analysis used multivariate analysis and simultaneous test (f test). The conclusions in this study are: (1) the results of the manova test with Sig. 0.043 < 0.05, therefore Ho is rejected and Ha is accepted, meaning that there is an influence between the Village Fund Allocation and Village Development (2) the results of the manova test of sig 0.000 < 0.05 so rejecting Ho and accepting Ha, which means there is a significant effect between The allocation of village funds to the welfare of the society (3) the results of the joint Manova test of Sig 0.001 < 0.05 so that Ho is rejected and Ha is accepted, which means that there is a significant influence between the allocation of village funds on village development and society welfare.